Frequency and characteristics of cardiac arrhythmias in adultstreated at the outpatient department of a high-altitude hospital - Diaz Lazo, Anibal Valentin (2026)
Objective: To determine the frequency and characteristics of cardiac arrhythmias in adults treatedat the outpatient department of a high-altitude hospital. Materials and methods: An observational, cross sectional, prospective study was conducted. The sample size was calculated using a formula. Inclusion criteria were age ≥ 18 years, both sexes, presence of palpitations, provision of informed consent to participate in the study, and having a 24-hour electrocardiographic recording. Exclusion criteria were acute infectious, cardiac, or metabolic disease; or mental illness. Results: A total of 250 participants (100.00%) were included. The median age was 62 years (interquartile range [IQR]: 27), and 62.80% (157) were women. Cardiac arrhythmias were more common in women than in men, at a ratio of 2:1. The proportion of affected individuals increased with age, reaching 48.92% among those aged 18–39 years and 100.00% among those aged ≥ 80 years. Cardiovascularrisk factors included hypertension in 40.80% (102), dyslipidemia in 20.40% (51), obesity in 16.80% (42), and sedentary lifestyle in 19.60% (49). The most frequent types of supraventricular arrhythmias were isolated supraventricular extrasystole in 70.40% (176), supraventricular tachycardia in 27.20% (68), supraventricular couplets in 16.40% (41), and atrial fibrillation in 8.00% (20). Ventricular arrhythmias included monomorphic ventricular extrasystole in 30.40% (76), polymorphic ventricular extrasystole in 6.80% (17), ventricular couplets in 5.20% (13), and non-sustained ventricular tachycardia in 3.60% (9). Bradyarrhythmias found were sinus pause in 2.00% (5), sinoatrial block in 0.40% (1), and second-degree atrioventricular (AV) block type II in 0.40% (1). Conclusions: The frequency of supraventricular arrhythmias was high, whereas ventricular arrhythmias were moderate. The most common types were simple supraventricular and ventricular extrasystoles.